2018
DOI: 10.1161/jaha.118.009244
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of MicroRNA‐155 Supports Endothelial Tight Junction Integrity Following Oxygen‐Glucose Deprivation

Abstract: BackgroundBrain microvascular endothelial cells form a highly selective blood brain barrier regulated by the endothelial tight junctions. Cerebral ischemia selectively targets tight junction protein complexes, which leads to significant damage to cerebral microvasculature. Short noncoding molecules called microRNAs are implicated in the regulation of various pathological states, including endothelial barrier dysfunction. In the present study, we investigated the influence of microRNA‐155 (miR‐155) on the barri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 50 publications
2
22
0
Order By: Relevance
“…OGD stimulation often triggers the aberrant miRNAs expression, like miR-7 [41], miR-155 [42], miR-132 [43], miR-27a [21]. Interestingly, Cai et al found that miR-27a overexpression attenuated OGD-induced injury in hippocampal neurons [21], which was consistent with our results.…”
Section: R E T R a C T E Dsupporting
confidence: 91%
“…OGD stimulation often triggers the aberrant miRNAs expression, like miR-7 [41], miR-155 [42], miR-132 [43], miR-27a [21]. Interestingly, Cai et al found that miR-27a overexpression attenuated OGD-induced injury in hippocampal neurons [21], which was consistent with our results.…”
Section: R E T R a C T E Dsupporting
confidence: 91%
“…As small EVs contain microRNAs, and because the effects that we observed took days (24–48 h), it is tempting to suggest that microRNAs from the EVs entered the target endothelial cells and led to gene expression changes for the different junction proteins. There have been a number of previous papers showing that microRNAs affect the expression of adherens and tight junction proteins in endothelial cells [ 29 , 30 , 31 , 32 , 33 , 34 ]. Although, not extensively studied in endothelial cells, there is strong evidence that several microRNAs (including miR-1, miR-130a, miR-206, and others) can downregulate Cx43 [ 35 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…First, Han et al reported increased circulating MIR155 levels in human sepsis [ 21 ]. Second, Pena-Philippides et al implicated MIR155 in the regulation of endothelial tight junctions after cerebral ischemia [ 22 ]. Specifically, they reported that inhibition of MIR155 fortified monolayers of human primary brain microvascular endothelial cells against barrier breakdown following oxygen–glucose deprivation.…”
Section: Discussionmentioning
confidence: 99%